Aqueous two-phase based on ionic liquid liquid–liquid microextraction for simultaneous determination of five synthetic food colourants in different food samples by high-performance liquid chromatography. (1st May 2015) - Sha, Ou; Zhu, Xiashi; Feng, Yanli; Ma, Weixing
Highlights: Colourants extracted into IL phase could be analysed by HPLC with direct sampling. The enhancement factors from 32 to 48 were obtained after ATPS extraction. The phase behaviours were studied by the ration phase and partition coefficient. Extraction mechanism could be explained by the salting-out effect. Variety wavelength was selected to get higher sensitivity and reduce the interference. Abstract: A rapid and effective method of aqueous two-phase systems based on ionic liquid microextraction for the simultaneous determination of five synthetic food colourants (tartrazine, sunset yellow, amaranth, ponceau 4R and brilliant blue) in food samples was established. High-performance liquid chromatography coupled with an ultraviolet detector of variable wavelength was used for the determinations. 1-alkyl-3-methylimidazolium bromide was selected as the extraction reagent. The extraction efficiency of the five colourants in the proposed system is influenced by the types of salts, concentrations of salt and [Cn MIM]Br, as well as the extracting time. Under the optimal conditions, the extraction efficiencies for these five colourants were above 95%. The phase behaviours of aqueous two-phase system and extraction mechanism were investigated by UV–vis spectroscopy. This method was applied to the analysis of the five colourants in real food samples with the detection limit of 0.051–0.074 ng/mL. Good spiked recoveries from 93.2% to 98.9% were obtained.